Long PDE4 cAMP specific phosphodiesterases are activated by protein kinase A-mediated phosphorylation of a single serine residue in Upstream Conserved Region 1 (UCR1) - MacKenzie, Simon J (2002)
1. Challenge of COS1 cells with the adenylyl cyclase activator forskolin led to the activation of recombinant PDE4A8, PDE4B1, PDE4C2 and PDE4D5 cAMP-specific phosphodiesterase long isoforms. 2. Forskolin challenge did not activate mutant long PDE4 isoforms where the serine target residue (STR) within the protein kinase A (PKA) consensus phosphorylation site in Upstream Conserved Region 1 (UCR1) was mutated to alanine. 3. The PKA inhibitor, H89, ablated forskolin activation of wild-type long PDE4 isoforms. 4. Activated PKA caused the in vitro phosphorylation of recombinant wild-type long PDE4 isoforms, but not those where the STR was mutated to alanine. 5. An antiserum specific for the phosphorylated form of the STR detected a single immunoreactive band for recombinant long PDE4 isoforms expressed in COS1 cells challenged with forskolin. This was not evident in forskolin-challenged cells treated with H89. Neither was it evident in forskolin-challenged cells expressing long isoforms where the STR had been mutated to alanine. 6. In transfected COS cells challenged with forskolin, only the phosphorylated PDE4D3 long form showed a decrease in mobility in Western blotting analysis. This decreased mobility of PDE4D3 was ablated upon mutation of either of the two serine targets for PKA phosphorylation in this isoform, namely Ser(54) in UCR1 and Ser(13) in the isoform-specific N-terminal region. 7. Activation by forskolin challenge did not markedly alter the sensitivity of PDE4A8, PDE4B1, PDE4C2 and PDE4D5 to inhibition by rolipram. 8. Long PDE4 isoforms from all four sub-families can be phosphorylated by protein kinase A (PKA). This leads to an increase in their activity and may thus contribute to cellular desensitization processes in cells where these isoforms are selectively expressed.